2019
DOI: 10.1021/acs.orglett.9b01434
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Enabled Chan–Lam Couplings of Aryl Boronic Acids and Anilines

Abstract: The Chan–Lam reaction remains a highly utilized transformation for C–N bond formation. However, anilines remain problematic substrates due to their lower nucleophilicity. To address this problem, we developed an electrochemically mediated Chan–Lam coupling of aryl boronic acids and amines utilizing a dual copper anode/cathode system. The mild conditions identified have enabled the preparation of a wide range of functionalized biarylanilines in good yields and chemoselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 24 publications
(51 reference statements)
0
30
0
Order By: Relevance
“…In 2019, Gale-Day and co-workers reported the electrochemical synthesis of a variety of N-arylanilines via the Chan-Lam coupling of anilines and arylboronic acids utilizing a dual copper anode/cathode system in the presence of Et 3 N and air or oxygen (Scheme 29). 35 Anilines with electron-rich substituents or with para-halo groups reacted well, whereas those bearing electron-deficient groups gave moderate yields. A variety of arylboronic acids bearing both electron-withdrawing and -donating groups underwent the reaction smoothly to furnish the products in good to excellent yields.…”
Section: Scheme 27 Cu(oac) 2 -Mediated Reaction Of Arylboronic Acid Pmentioning
confidence: 99%
“…In 2019, Gale-Day and co-workers reported the electrochemical synthesis of a variety of N-arylanilines via the Chan-Lam coupling of anilines and arylboronic acids utilizing a dual copper anode/cathode system in the presence of Et 3 N and air or oxygen (Scheme 29). 35 Anilines with electron-rich substituents or with para-halo groups reacted well, whereas those bearing electron-deficient groups gave moderate yields. A variety of arylboronic acids bearing both electron-withdrawing and -donating groups underwent the reaction smoothly to furnish the products in good to excellent yields.…”
Section: Scheme 27 Cu(oac) 2 -Mediated Reaction Of Arylboronic Acid Pmentioning
confidence: 99%
“…Intrigued by this previous report, 53 work in our lab focused on the application of electrochemical mediation to the traditional Chan-Lam reaction. 54 Specifically, the substrate scope focused on traditionally challenging electronpoor boronic acid coupling partners. Using inexpensive copper(II) acetate as the catalyst, good to excellent yields were achieved for a series of electron-poor boronic acids.…”
Section: Scheme 13 Electrochemical Synthesis Of Phenols and Aniline Umentioning
confidence: 99%
“…[ 16 ] Afterwards, Wexler et al reported an electrocatalytic coupling of arylboronic acids with amines by a dual copper anode/cathode system. [ 17 ] Soon after, copper‐catalyzed anaerobic Chan–Lam reaction between arylboronic acids and various amines with electrochemistry in replace of strong chemical oxidants was also achieved by Sevov's group. [ 18 ] Very recently, Di et al documented the coupling of 2‐aminopyridine and arylboronic acid to furnish N ‐arylpyridin‐2‐amine derivatives via irradiation of blue light using copper modified phosphorus‐doped g‐C 3 N 4 (Cu/P‐CN) as a heterogeneous photocatalyst.…”
Section: Introductionmentioning
confidence: 99%